Linear IgA bullous dermatosis - L. F. Znamenskaya; V. V. Chikin; M. A. Nefedova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Aim: to present a clinical case of linear IgA bullous dermatosis.Materials and methods. A 44 years old patient complaining of skin rashes on the trunk and extremities, accompanied by severe itching was examined. We carried out a morphological investigation of biopsy samples derived from the lesion and apparently unaffected skin areas using the method of indirect immunofluorescence.Results. The patient having rashes in the form of multiple vesicles and small bubbles with a tight cover, which had been grouped into figures resembling pearl necklaces, demonstrated the presence of focal subepidermal cracks (subepidermal bubble in one location), as well as a linear deposition of IgA along the epidermal basement membrane. According to the clinical picture and following the histological and immunofluorescent investigation of skin biopsies, the patient was diagnosed with linear IgA bullous dermatosis. Lesion regression was achieved as a result of systemic therapy with prednisolone at a dose of 50 mg per day.Conclusion. The diagnosis of linear IgA bullous dermatosis should be made on the basis of skin biopsy investigation by the method of indirect immunofluorescence. Systemic glucocorticosteroids are seen as an effective approach to the treatment of such patients.